Public perception on family environment and its relationship on teenagers deviant behavior: A case study in Melaka Tengah, Melaka / Muhamad Hafiz Ab Razak and Muhd Shaiful Idzham Muhd Shaifudin - Ab Razak, Muhamad Hafiz; Muhd Shaifudin, Muhd Shaiful Idzham (Faculty of Administrative Science and Policy Studies, 2013)
This study had been carried out to identify the relationship between family environment and teenager’s deviant behavior among public perception in Melaka Tengah, Melaka. The sample size of population is 100 respondents. The sampling technique that been used is non probability sampling. The objective of this research is to identify whether parental behavior, parenting skills and family communication have a relationship or not with the teenager’s deviant behavior. The findings of this research indicate that parental behavior, parenting skills and family communication have a relationship with the teenager’s deviant behavior. This research provides significant information to the family, public and also teenagers itself.